Desgaste corrosivo-cavitativo-erosivo de um aço-carbono em meio aquoso com frações de sal (NaCl), CO2 e particulados sólidos (SiO2) - Silva, Fernando Nunes da (2012)
A batch of eighty-four coupons of low carbon steel were investigated at laboratory conditions under a corrosive, cavitative-corrosive (CO2) and corrosive-erosive (SiO2 + CO2) in an aqueous salt solution and two levels of temperature. The following measurements were made on Vickers (HV0,05, HV0,10, HV0,20) Microhardness tests at three levels of subsurface layer. A turbulent flow collided on the cylindrical sample, with and without mechanical stirring and gas bubbling, with and without fluid contamination by solid particles of SiO2, at two temperatures. Surface Roughness and Waviness, under two conditions "as received, after machining" and "after worn out", as well as gravimetric and electrochemical parameter were measured on the two opposite generatrices of each cylindrical sample, on the flow upstream (0°) and downstream (180°) by Profilometry, Mass Variation and Linear Polarization Resistance (LPR). The results of the Microhardness and Surface Texture of all coupons were subjected to statistical comparison, using the software Statgraphics® Centurion XVI, 95% statistical certainty, and significant differences were observed in some arrays of measurements. The corrosive wear rate measured by LPR and mass variation shown to be sensitive to the presence of bubbles and hydrodynamic fluctuations inside the cell, considering the temperature and contamination of corrosive fluid by solid particles. The main results of visual inspection relative to some topologies of the surface damages involving different mechanisms that were seen to give explanation for some fluctuations in wear rates of the steel experimentally investigated